Ranges and Movements of Montezuma Quail in Southeast Arizona - Pedro M. Chavarria; Nova J. Silvy; Roel R. Lopez; Donald S. Davis; Angel Montoya (National Quail Symposium Proceedings, 2017)
Historical assumptions about Montezuma quail movements and home ranges at the population level are limited due to the lack of markrecapture studies on this species from which solid conclusions can be derived. Such information is crucial for estimating population sizes, densities, and rate of emigration and immigration throughout the landscape. Our study examined home range size of 29 Montezuma quail and movements of 65 quail in southeast Arizona from 2008–2010. We used radio telemetry to follow radio-tagged birds in 3 study sites that varied in vegetation composition and topography. Mean home range size (MCP) was about was similar (51 ha) to the largest use area (50 ha) described in the literature for this species. The largest MCP home range estimate (206.7 ha) was far larger than what has been reported in the literature. Within a season, the largest mean maximum distance moved between 2 locations was 1,128.4 ± 619.5 m and the largest maximum linear distance between 2 locations for an individual was 2,375.5 m. Results from our research should help to address knowledge gaps about Montezuma quail home ranges and movements and provide a baseline to assist management of this species in the future.
Keywords: Cyrtonix montezumae; home range; Mearn' s quail; Montezuma quail; movements